The constraints of good governance practice in National Solid Waste Management Policy (NSWMP) implementation in Malaysia - Abas, Muhamad Azahar; Wee, Seow Ta (American Scientific Publishers, 2017)
Solid waste production in the urban area has risen alarmingly fast of late. The situation is becoming crucial thus an effective solid waste management is greatly needed. International donors emphasised on the adoption of good governance practices in solid waste management which include policy implementation. In Malaysia, the National Solid Waste Management Policy (NSWMP) was introduced as the main guideline for its solid waste management and the Malaysian government has adopted good governance practice in the NSMWP implementation. However, the good governance practices implemented by the Malaysian government encountered several challenges. This study was conducted to explore the good governance constraints experienced by stakeholders in the NSWMP implementation. An exploratory research approach is applied in this study through in-depth interviews with several government agencies and concessionaires that involved in the NSWMP implementation in Malaysia. A total of six respondents took part in this study. The findings revealed three main good governance constraints in the NSWMP implementation, namely inadequate fund, poor staff’s competency, and ambiguity of policy implementation system. Moreover, this study also disclosed that the main constraint influenced the other constraints. Hence, it is crucial to identify the main constraint in order to minimise its impact on the other constraints. Finally, recommendations for good governance improvement are suggested based on the identified constraints. This study will provide an insight to the Malaysian government in particular on an effective solid waste management.